The diagnostic efficacy of apparent diffusion coefficient value and Choline/Creatine ratio in differentiation between parotid gland tumors - Mai E.M. Khamis; Ayman F. Ahmed; Eman I. Ismail; Mohamed F. Bayomy; Mohammad W. El-Anwar (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Objective: To detect the diagnostic performance of apparent diffusion coefficient (ADC) value and Cho/Cr ratio in distinguishing various pathological subtypes of parotid gland tumors. Patients and Methods: This study included 30 patients (14 males and 16 females; age ranged from 25 to 70 years; mean age 50 ± 12.5 years) with 31 parotid gland masses. Diffusion weighted imaging and MR spectroscopy were performed in all patients. ADC values and Cho/Cr ratios were measured for each parotid mass and compared with pathology. The diagnostic performance of ADC value, Cho/Cr ratio, ADC + Cho/Cr ratio and ADC × Cho/Cr ratio for differentiating pathological subtypes were assessed. Results: Pleomorphic adenomas had highest ADC values and Warthin tumors had highest Cho/Cr ratios. ADC value had the best diagnostic performance in differentiating pleomorphic adenomas from Warthin tumors by using cutoff value 1.12 × 10−3 mm2/sec with sensitivity, specificity, PPV, NPV and accuracy 100% for each. ADC value × Cho/Cr ratio had the best diagnostic performance in differentiating malignant from benign tumors, malignant tumors from pleomorphic adenoma and malignant from Warthin’s tumors by using cutoff value 2.37 at which sensitivity, specificity, PPV, NPV and accuracy all were 100%. Conclusion: ADC value and Cho/Cr ratio are useful in differentiating different pathological subtypes of parotid tumors.